2019
DOI: 10.1098/rspb.2018.1887
|View full text |Cite
|
Sign up to set email alerts
|

Future climate change is predicted to affect the microbiome and condition of habitat-forming kelp

Abstract: Climate change is driving global declines of marine habitat-forming species through physiological effects and through changes to ecological interactions, with projected trajectories for ocean warming and acidification likely to exacerbate such impacts in coming decades. Interactions between habitat-formers and their microbiomes are fundamental for host functioning and resilience, but how such relationships will change in future conditions is largely unknown. We investigated independent and interactive effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(123 citation statements)
references
References 62 publications
4
103
0
Order By: Relevance
“…Future studies should investigate the microbiome differences among Daphnia isolates immediately post-collection from across a latitudinal gradient and look at the role of temperature fluctuations on microbiome content and stability. Other studies of microbiome response in near-future temperature regimes have shown a wide range of patterns (from no variation to major variation affecting microbiome functionality), suggesting the need for more research [2,32]. Further investigation, with reproducible results, looking into whether shifts in microbiota are common across temperature gradients (in nature and in the laboratory) will clarify our understanding of how such factors might shape microbiome variation as climates change.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Future studies should investigate the microbiome differences among Daphnia isolates immediately post-collection from across a latitudinal gradient and look at the role of temperature fluctuations on microbiome content and stability. Other studies of microbiome response in near-future temperature regimes have shown a wide range of patterns (from no variation to major variation affecting microbiome functionality), suggesting the need for more research [2,32]. Further investigation, with reproducible results, looking into whether shifts in microbiota are common across temperature gradients (in nature and in the laboratory) will clarify our understanding of how such factors might shape microbiome variation as climates change.…”
Section: Discussionmentioning
confidence: 97%
“…Further, we test if D. magna microbiomes from these nine genotypes vary when raised in different temperatures under laboratory conditions. We hypothesized that population-of-origin and temperature (and, potentially, their interaction) would exhibit an effect on microbiota given that bacteria have been shown to vary across temperatures in other systems ( [2,32]), and the history of different temperatures experienced by the isolates we tested may have shaped their capacity for hosting different bacteria. We compare our results to those of Sullam et al [44], who also examined whether population ("host clonal line") or temperature affects the microbiome, although several aspects of their study design differed from ours.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, understanding drivers of interspecific microbiome variability is important in the context of global climate change. Ocean warming and acidification are predicted to change microbial communities both within the environment and in host‐associated microbiomes, with huge implications for health and survival of marine species and their ecosystems (Lesser, Fiore, Slattery, & Zaneveld, ; Qiu et al, ). For example, ocean warming in the Mediterranean triggered microbial imbalances in I. fasciculata , which have been implicated in disease and mass mortalities (Blanquer, Uriz, Cebrian, & Galand, ).…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing number of studies and models showing such interactions, it has been shown that the chemical production at the surface of algae may represent one of the main parameter driving the dynamic of epiphytic microbial communities (Nylund et al, 2010;Lachnit et al, 2013;Saha et al, 2014). In addition, environmental parameters also seem to be involved in the shaping of surface microbiota of seaweed holobionts such as Fucus vesiculosus, Ecklonia radiata, Caulerpa prolifera, Caulerpa cylindracea, Macrocystis pyrifera, Delisea pulchra, and Sargassum muticum (Stratil et al, 2013(Stratil et al, , 2014Marzinelli et al, 2015Marzinelli et al, , 2018Zozaya-ValdĂ©s et al, 2016;Aires et al, 2018;Minich et al, 2018;Morrissey et al, 2019;Qiu et al, 2019). Nevertheless, while the microbial communities associated with the surface of algae are increasingly studied, the chemical composition of the surface of the algal hosts and the variations of the metabolic production at the thallus scale have been only rarely investigated to date.…”
Section: Introductionmentioning
confidence: 99%